1999
DOI: 10.1093/humrep/14.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Previously undetected Chlamydia trachomatis infection, immunity to heat shock proteins and tubal occlusion in women undergoing in-vitro fertilization

Abstract: The relationship between a previously undetected Chlamydia trachomatis infection, tubal infertility, immunity to heat shock proteins and subsequent in-vitro fertilization (IVF) outcome was evaluated. Women with tubal occlusion, with or without hydrosalpinges, and no history of C. trachomatis infection were tested for circulating antibodies to the human 60-kDa heat shock protein (Hhsp60), the C. trachomatis 10-kDa heat shock protein (Chsp10) and C. trachomatis surface antigens prior to their initial IVF cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 14 publications
3
19
1
Order By: Relevance
“…A number of studies have shown that both humoral and cell-mediated immune responses to the chlamydial hsp60, as well as the generation of immune responses that recognize the human hsp60, contribute to the pathogenesis of a chlamydial genital tract infection (65)(66)(67)(68). It should be noted that when C. trachomatis was added to a fallopian tube organ culture, only minimal damage was noted (69).…”
Section: The C Trachomatis 60-kda Heat Shock Proteinmentioning
confidence: 99%
“…A number of studies have shown that both humoral and cell-mediated immune responses to the chlamydial hsp60, as well as the generation of immune responses that recognize the human hsp60, contribute to the pathogenesis of a chlamydial genital tract infection (65)(66)(67)(68). It should be noted that when C. trachomatis was added to a fallopian tube organ culture, only minimal damage was noted (69).…”
Section: The C Trachomatis 60-kda Heat Shock Proteinmentioning
confidence: 99%
“…This has largely resulted from a body of literature demonstrating high-titer human antibody responses to cHSP60 in patients with tubal pathology and additionally that, in several animal models, tissue pathology developed after repeated inoculations with cHSP60 protein (reviewed in reference 138). However, this mechanism is a subject of considerable controversy because of inconsistencies between the different published findings, i.e., problems with protein preparations that involved a hypersensitive detergent being used in some animal models and cross-reactivity or poor specificity of some of the antibody tests (141)(142)(143)(144)(145)(146)(147). On the other hand, there is no doubt that cHSP60 is a predominant chlamydial antigen that does frequently elicit an immune response.…”
Section: Chsp60-induced Delayed Hypersensitivitymentioning
confidence: 99%
“…Viable C. trachomatis can also persist in macrophages, and this may provide an alternative target cell for chlamydial replication in a number of infections; follicular fluid contains tissue macrophages in large amounts (14). Other authors suggested that in these patients the poor IVF outcome was associated with subclinical chlamydial infection (19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%